2019
DOI: 10.1021/acsbiomaterials.9b00146
|View full text |Cite
|
Sign up to set email alerts
|

PMMA Bone Cement Acts on the Hippo/YAP Pathway To Regulate CTGF and Induce Intervertebral Disc Degeneration

Abstract: Kyphoplasty is a novel approach treating osteoporotic vertebral compression fractures and poly­(methyl methacrylate) (PMMA) is the most common bone cement used for kyphoplasty. Cement leaked into an intervertebral disc (IVD) usually causes problems. Herein, we explored the effects of PMMA particles on the biological behavior of nucleus pulposus cells and proved the inhibiting effect of PMMA particles in a dose-dependent manner. Besides, PMMA particles led to cell cycle arrest and the abnormal expression of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Regarding the biological level of whether or how bone cement particles may induce IDD, which is the main aim of our study, our group has previously done some research on the biological mechanism of how PMMA particles induce HNPCs’ degeneration [ 29 ]. That study revealed the role of PMMA particles in inducing IVD degeneration by downregulating CTGF through Hippo/YAP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the biological level of whether or how bone cement particles may induce IDD, which is the main aim of our study, our group has previously done some research on the biological mechanism of how PMMA particles induce HNPCs’ degeneration [ 29 ]. That study revealed the role of PMMA particles in inducing IVD degeneration by downregulating CTGF through Hippo/YAP pathway.…”
Section: Discussionmentioning
confidence: 99%
“…No.4800). Cell culture was performed as described in the protocol in our previous study [22]. Cells preserved in liquid nitrogen were quickly thawed in a preheated water bath (37°C) for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability of NPCs was determined at 24 h and 96 h after the induction with 0.1, 0.5, 1, 5, 10, 50, and 100 μ M melatonin. The measurement procedure was as described in our previous study [22]: 10 μ L of Cell Counting Kit-8 (CCK-8) solution (Dojindo, Tokyo, Japan) was added to each well and the 96-well plates were incubated for 1 h at 37°C and 5% CO 2 . After that, the supernatants were carefully aspirated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations